Using an SQL coverage measurement for testing database applications. - Suárez-Cabal, María José (Software engineering notes.)
Many software applications have a component based on database management systems in which information is generally handled through SQL queries embedded in the application code. When automation of software testing is mentioned in the research, this is normally associated with programs written in imperative and structured languages. However, the problem of automated software testing applied to programs that manage databases using SQL is still an open issue. This paper presents a measurement of the coverage of SQL queries and the tool that automates it. We also show how database test data may be revised and changed using this measurement by means of completing or deleting information to achieve the highest possible value of coverage of queries that have access to the database.